2020
DOI: 10.1038/s41598-020-73315-6
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence-mediated exacerbation of Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a progressive disease characterised by chronic muscle degeneration and inflammation. Our previously established DMD model rats (DMD rats) have a more severe disease phenotype than the broadly used mouse model. We aimed to investigate the role of senescence in DMD using DMD rats and patients. Senescence was induced in satellite cells and mesenchymal progenitor cells, owing to the increased expression of CDKN2A, p16- and p19-encoding gene. Genetic ablation of p16 in DMD rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 78 publications
3
90
0
Order By: Relevance
“…Notably, the senolytic action of ABT-263 appears to depend on inhibition of BCL-X L and/or BCL-W, while BCL-2 inhibition is dispensable [84,86]. Similar to D+Q, ABT-263 was successful in eliminating senescent cell populations in several disease models including aging-associated bone loss [87], radiation-induced lung fibrosis [88], lung emphysema [89], uterine leiomyoma [90], tau-dependent neurodegenerative disease [91], radiation-induced neurodegeneration [92], myocardial infarction (including ischemia-reperfusion injury) [93,94], heart failure [95], pulmonary hypertension [96], insulin resistance [97], osteoarthritis [98,99], synthetic implant-mediated fibrosis [100], and Duchenne muscular dystrophy [101]. ABT-263 is currently a cornerstone in preclinical studies of senolysis and remains a promising drug for use against both liquid and solid tumors [102][103][104].…”
Section: Senolytic Therapies: Have We Hit Gold or Pyrite? 21 Establmentioning
confidence: 99%
“…Notably, the senolytic action of ABT-263 appears to depend on inhibition of BCL-X L and/or BCL-W, while BCL-2 inhibition is dispensable [84,86]. Similar to D+Q, ABT-263 was successful in eliminating senescent cell populations in several disease models including aging-associated bone loss [87], radiation-induced lung fibrosis [88], lung emphysema [89], uterine leiomyoma [90], tau-dependent neurodegenerative disease [91], radiation-induced neurodegeneration [92], myocardial infarction (including ischemia-reperfusion injury) [93,94], heart failure [95], pulmonary hypertension [96], insulin resistance [97], osteoarthritis [98,99], synthetic implant-mediated fibrosis [100], and Duchenne muscular dystrophy [101]. ABT-263 is currently a cornerstone in preclinical studies of senolysis and remains a promising drug for use against both liquid and solid tumors [102][103][104].…”
Section: Senolytic Therapies: Have We Hit Gold or Pyrite? 21 Establmentioning
confidence: 99%
“…Similarly, the cell surface protein Cdon, which positively regulates myogenesis, is downregulated in progeria model mice, and MuSC-specific knockout of Cdon promotes γH2AX expression in MuSCs after injury, resulting in impaired muscle regeneration ( Bae et al, 2020 ). In addition to aging, obesity and muscular dystrophy are associated with accumulation of senescent MuSCs ( Kudryashova et al, 2012 ; Mu et al, 2015 ; Roux et al, 2015 ; Zhang et al, 2016 ; Dungan et al, 2020 ; Sugihara et al, 2020 ). Although the disease-specific mechanism of senescence induction remains unknown, senescence in MuSCs can result from reduced mitophagy, TGF-β–induced Smad3 activation, and over-activation of Notch ( Figure 1 ) ( Carlson et al, 2008 ; Mu et al, 2015 ; García-Prat et al, 2016 ).…”
Section: Senescence In Skeletal Musclementioning
confidence: 99%
“…Interestingly, mouse knockouts of two other senescence-related genes, p53 and p21 (BubR1H/H; p53-/- and BubR1H/H; p21-/-) impairs the muscle regeneration capacity of the BubR1H/H mice ( Baker et al, 2013 ). Another study reported that senescent FAPs are more abundant in obese humans and a rat model of Duchenne muscular dystrophy; however, the causal link between the increased senescent FAPs and muscle pathology remains unclear ( Dungan et al, 2020 ; Sugihara et al, 2020 ).…”
Section: Senescence In Skeletal Musclementioning
confidence: 99%
See 2 more Smart Citations